A Path Analysis of Socialization Model in Traditional Market: Behavior, Function, Visual Exposure, and Access and Communication. (7th January 2020) - Najjari Nabi, Rana; Mahdinezhad, Jamaloddin; Saleh Sedghpour, Bahram
Abstract: Public spaces serve as an important site of social interaction. They allow people to gather and socialize away from home and work. This article discusses the meaning of urban public space and its role in the socialization of users in the market and the discussion of public space as a part of the socialization of businessmen and people who meet there for shopping, recreation, and establishing social relationships. The purpose of this study was to test a conceptual model, using path analysis to examine direct and indirect relationships among factors contributing socialization in the public traditional Iranian Bazaars. Included in a path analysis were 326 cases. As hypothesized, behavior, function, visual exposure, and access and communication of 12 components were found to be effective factors that positively influenced socialization of markets.